173k views
0 votes
How do you do this???

Please explain how it goes from This------> 10-6x=4+5x to This----> 7-6x=1+5x

User Bjoern
by
5.6k points

1 Answer

4 votes

10-6x=4+5x

-3 from both sides

7-6x=1+5x

Explanation:

if you want the answer to the actual thing then here:

10-6x=4+5x

+6x

10=4+11x

-4

6=11x

÷11

0.54≈ x

(I rounded it to 2dp which is why it has the squiggly equal sign to show that it is not quite equal but is an estimation of some kind

User Christian Lescuyer
by
5.0k points